Fathi Yakan dan Sumbangannya dalam Bidang Pemikiran Islam: Fathi Yakan and His Contributions in Islamic Thought - Mohaiyuddin, Asma Kholilah; Sahad, Mohd Nizam (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
Islamic thought began to gain recognition of intellectual debate over Muslim and non-Muslim scholars, thus the development of knowledge and the escalation of prominent scholars. Over the years, writing had been the chosen medium for Islamic thinkers to express and disseminate their views and thoughts on certain issues or problems. Fathi Yakan, a prominent figure of the field of da’wah, politics and Islamic movement also makes writing to propagate his knowledge and thoughts. His books are well received all over the world and have been translated into various languages worldwide. This article aims to review his contributions to the field of Islamic thought. Library research was conducted to obtain data onto Fathi Yakan and his contributions to the field of Islamic thought. This study found that Fathi Yakan had contributed significantly to the field of Islamic thought through his books encompassing `aqidah, politics, Islamic movements, education, da’wah and economic.